Herbicide selectivity on macauba seedlings and weed control efficiency - Santos da Costa, Yanna Karoline [UNESP]; Lopes de Freitas, Francisco Claudio; Silveira, Hellen Martins da; Mendes Nascimento, Roxana Stefane; Sediyama, Carlos Sigueyuki; Alcantara-de la Cruz, Ricardo (Elsevier B.V., 2020)
Seedlings of macauba (Acrocomia aculeata (Jacq.) Lodd. ex Mart) palm spend similar to 10 months in nursery before being taken to the field. Since there are no registered herbicides for macauba, weed control in seedling containers is done manually; however, macauba leaves have thorns that injure workers' hands. In this work, the selectivity of indaziflam, isoxaflutol, oxyfluorfen and sulfentrazone was evaluated on macauba seedlings produced in nurseries, incorporated (INC) to the substrate and/or applied before (PRE) and after (POST) transplantation, as well as its efficacy for the weed control. Seedlings were no intoxicated by the herbicides regardless of the application method. However, considering the height, leaf area and dry weight and root volume, the INC and PRE applications of indaziflam were not selective for macauba. In contrast, POST-indaziflam applications stimulated the growth of seedlings (< 100 cm), being even greater than the control (75 cm) M 10 months. Regarding weed control, the INC treatments lost effectiveness up to 40 % from 14 to 56 days after application (DAA), except indaziflam which maintained a control above 95 %. Weed control of PRE applications decreased up to 60 % for all four herbicides, while the POST applications of indaziflam, oxyfluorfen and sulfentrazone maintained control levels >= 80 % at the same period. Weed presence reduced the growth rate of macauba seedlings by similar to 40 % (32 cm high in the non-weeding control vs 55 cm in the weeding control) at 126 DAA. In addition, weeds reduced the growth of seedlings in most treatments, since the plant height was similar to the non-weeding control. Isoxaflutole, oxyfluorfen and sulfentrazone were selective for macauba seedlings, regardless of the herbicide application method. Indaziflam was selective for seedlings only in POST applications. The evaluated herbicides were efficient in controlling most weed species up to 56 DAA in PRE and POST applications.
Keywords: Acrocomia aculeata; Indaziflam; Isoxaflutole; Oxyfluorfen; Sulfentraozne